A novel oncolytic Vaccinia virus armed with IL-12 augments antitumor immune responses leading to durable regression in murine models of lung cancer - Chen, Lijuan; Wang, Pengju; Di Gioia, Carmela; Yuan, Ming; Zhang, Zhe; Miao, Jinxin; Yan, Wenli; Zhao, Guanghao; Jia, Yangyang; Wang, Na; Zhang, Zhongxian; Guo, Haoran; et al. (Frontiers in Immunology, 2025)
Oncolytic vaccinia viruses (VVs) are potent stimulators of the immune system and induce immune-mediated tumor clearance and long-term surveillance against tumor recurrence. As such they are ideal treatment modalities for solid tumors including lung cancer. Here, we investigated the use of VVL-m12, a next-generation, genetically modified, interleukin-12 (IL-12)-armed VV, as a new therapeutic strategy to treat murine models of lung cancer and as a mechanism of increasing lung cancer sensitivity to antibody against programmed cell death protein 1 (α-PD1) therapy. The cytotoxicity and replication of VVL-m12, VVL-h12 and control VVs were assessed in lung cancer cell lines. Subcutaneous lung cancer mouse models were established to investigate the anti-tumor activity of the viruses after intratumoral delivery in an immunocompetent disease model. Synergy with α-PD1 or a VV armed with soluble PD-1 (VV-sPD1) was investigated and functional mechanisms behind efficacy probed. Tumor-targeted VVL-m12 replicated to high levels, was cytotoxic in lung cancer cell lines. VVL-m12 demonstrated superior antitumor efficacy in subcutaneous lung cancer models compared with other VVs examined. Importantly, rational combination of VVL-m12 and PD-1 blockade worked synergistically to significantly enhance survival of animals and safely cured lung cancer with no evidence of recurrence. VVL-m12 therapy induced increased intratumoral infiltration of CD4+ and CD8+ T cells and was able to clear tumor at early time points via increased induction and infiltration of effector T cells and central memory T cells (TCM). In addition, VVL-m12 increased dendritic cell activation, induced polarization of M2 macrophages towards an M1 phenotype, and inhibited tumor angiogenesis in vivo. These results demonstrate that VVL-12 has strong potential as a safe and effective antitumor therapeutic for lung cancer. Importantly, VVL-12 can sensitize lung cancers to α-PD1 antibody therapy, and the combined regime creates a highly effective treatment option for patients.